Cytoarchitectural modifications and antiinflammatory strategies in tendinopathy recovery - Marta Ramos-Barbero; Eva E. Rufino-Palomares; Sergio Serrano-Carmona; Cristina E. Trenzado; Khalida Mokhtari; José Antonio Lupiáñez; Amalia Pérez-Jiménez (PLoS ONE, 2025)
Tendinopathies (TPs) are complex conditions marked by inflammation, pain, and impaired function, often due to tendon overuse. Achilles tendinitis, a prevalent TP, affects both athletes and the general population. Despite available treatments, effective tissue regeneration remains elusive. This study investigates the molecular cytoarchitecture and protein expression in TP-related inflammation and evaluates the therapeutic potential of hydroxytyrosol (HT), maslinic acid (MA), glycine/aspartic acid (AA), and their combination with percutaneous intratissue electrolysis (EPI) in a Wistar rat model of induced TP. Animals received a diet supplemented by incorporating the compounds directly into the chow with MA (0.65 g/kg of diet), HT (3 g/kg of diet), and Gly/Asp (Gly: 28.125 g/kg of diet; Asp: 9.375 g/kg of diet). Tendon samples were collected at different TP phases (I, I-II, II, III). Histological analysis (H&E and Masson’s staining) assessed collagen fiber orientation, fibroblast density, and inflammation. Western blotting quantified inflammatory and apoptotic proteins (GST, Hsp60, JNK, NF-κB, PPAR‐γ, p53), while MDA levels indicated oxidative tissue damage. Results demonstrated that combining EPI with nutritional supplementation significantly improved recovery compared to EPI alone. Among the compounds tested, HT showed the most potent effects, followed by MA, reducing inflammation markers and enhancing tendon regeneration. Additionally, MDA levels significantly decreased in the HT group, indicating reduced oxidative stress. In cases where EPI is contraindicated, nutritional supplementation may serve as a viable non-invasive alternative, promoting faster healing and improved long-term outcomes. These findings highlight the potential of integrating EPI and targeted nutritional strategies to optimize TP treatment.